Problematyka etyki biznesu w edukacji przedsiębiorczości - Nowak, Kazimierz (Przedsiębiorczość - Edukacja, 2008)
Business activity should be managed in accordance with the moral appraisals and the normsuniversally accepted by given society. Moral appraisals and norms result from the value systemwhich guides peoples behavior. The business ethics task is to define what and why is moraland immoral in economic activity.Every entrepreneur ought to respect common ethical norms to sustain public trust.The principles of ethical practice are: hard work, honesty, perseverance, truthfulness, loyalty,justice, compassion (empathy), respect, trust and goodwill.The aim of business in the free market economy is profits, but human being is of the greatestvalue. Therefore, one should act in a way to gain profits and at the same time treat peoplehumanly not instrumentally, and respect their right to life, health, and dignity.Entrepreneurs on the market do not always use economic freedom in an honest way. Themost common forms of the ethical violation include: dishonest advertising, dumping, creativeaccounting, hiding profits, corruption.Corruption is the most dangerous phenomenon next to unfair competition and tax cheating.According to a ranking released by Transparency International, the level of corruption in stabledemocracies is much lower than in undemocratic countries.Firms undertaking ethical activities gain a desired advantage on the market. For the reasonthe management of such firms often treats business ethics as a tool in competitive struggle.How to combine business with ethics? Ethical view enables us to refer to the human being increation the economic models, and allows formulating the more realistic conception of entrepre-neurial person.